2008
DOI: 10.1074/jbc.m804159200
|View full text |Cite
|
Sign up to set email alerts
|

Selective Targeting of Leukemic Cell Growth in Vivo and in Vitro Using a Gene Silencing Approach to Diminish S-Adenosylmethionine Synthesis

Abstract: We exploited the fact that leukemic cells utilize significantly higher levels of S-adenosylmethionine (SAMe) than normal lymphocytes and developed tools that selectively diminished their survival under physiologic conditions. Using RNA interference gene silencing technology, we modulated the kinetics of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Recent studies in breast cancer cells suggest that SAM rather than methionine might be the limiting metabolite defining addiction to this metabolic pathway (Booher et al, 2012). Consistent with this idea, targeting methionine adenosyltransferase (MAT) with either a small molecule inhibitor or shRNA induces apoptosis in leukemia cells (Attia et al, 2008;Jani et al, 2009). The mechanisms of how cells induce cell cycle arrest and apoptosis in response to SAM limitation is currently unknown, but experiments in the yeast and breast cancer cell models indicate loss of pre-replication complexes from chromatin as a contributing factor (Booher et al, 2012;Su et al, 2005).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Recent studies in breast cancer cells suggest that SAM rather than methionine might be the limiting metabolite defining addiction to this metabolic pathway (Booher et al, 2012). Consistent with this idea, targeting methionine adenosyltransferase (MAT) with either a small molecule inhibitor or shRNA induces apoptosis in leukemia cells (Attia et al, 2008;Jani et al, 2009). The mechanisms of how cells induce cell cycle arrest and apoptosis in response to SAM limitation is currently unknown, but experiments in the yeast and breast cancer cell models indicate loss of pre-replication complexes from chromatin as a contributing factor (Booher et al, 2012;Su et al, 2005).…”
Section: Discussionmentioning
confidence: 49%
“…This idea is reminiscent of the SAM checkpoint proposed in the model organism S. cerevisiae (Kaiser et al, 2006). Consistent with this notion, targeted inhibition of MAT with a chemical inhibitor or shRNA knockdown was shown to inhibit leukemia cell proliferation and induce apoptosis (Attia et al, 2008;Jani et al, 2009), suggesting not only the existence of a SAM checkpoint in mammalian cells but also its potential as a therapeutic target. Furthermore, recent reports indicate breast and prostate cancer cells suffer a G1 cell cycle arrest when cultured in medium where methionine is replaced with its metabolic precursor homocysteine (Booher et al, 2012;Lu and Epner, 2000), probably as a consequence of reduced flux through the homocysteinemethionine-SAM metabolic axis, which results in insufficient SAM to support cell cycle progression (Booher et al, 2012).…”
Section: Introductionmentioning
confidence: 53%
“…Targeted inhibition of the regulatory subunit of MAT reduced SAM levels and strongly induced apoptosis and growth inhibition of leukemic cells. 16,17 Given such high demand for methionine and SAM by cancer cells, it is conceivable that replacement of methionine by homocysteine curtails flux through methyl group metabolism reducing methionine to a level insufficient for the high methionine requirement of cancer cells, thus affecting a cell cycle arrest and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Furthermore, earlier studies showed that reducing SAM synthesis blocks proliferation of leukemic cells. 16,17 Therefore, we hypothesized that methionine dependence is a reflection of limiting SAM availability caused by reduced flux through the methionine metabolic pathway in Met-Hcy+ conditions. Consistent with our hypothesis, SAM supplementation restored proliferation of MDAMB468 cells in Met-Hcy+ medium (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mutations involving the MAT1A gene have links with hepatic MAT deficiency which leads to hypermethioninemia (6,7). Expression of MATα2 confers a growth advantage in cells and is important for differentiation and apoptosis (1) in diseases such as human hepatocellular carcinoma (5), colon cancer (8), and leukemia (9).…”
mentioning
confidence: 99%